A pulse coding and decoding strategy to perform Lamb wave inspections using simultaneously multiple actuators. (July 2017) - De Marchi, Luca; Marzani, Alessandro; Moll, Jochen; Kudela, Paweł; Radzieński, Maciej; Ostachowicz, Wiesław
Highlights: Simultaneous excitation of multiple transducers in guided wave structural health monitoring systems. Damage imaging for spread spectrum coded pulses. Warped cross-correlation for pulse compression and dispersion compensation. Abstract: The performance of Lamb wave based monitoring systems, both in terms of diagnosis time and data complexity, can be enhanced by increasing the number of transducers used to actuate simultaneously the guided waves in the inspected medium. However, in case of multiple simultaneously-operated actuators the interference among the excited wave modes within the acquired signals has to be considered for the further processing. To this aim, in this work a code division strategy based on the Warped Frequency Transform is presented. At first, the proposed procedure encodes actuation pulses using Gold sequences. Next, for each considered actuator the acquired signals are compensated from dispersion by cross correlating the warped version of the actuated and received signals. Compensated signals form the base for a final wavenumber imaging meant at emphasizing defects and or anomalies by removing incident wavefield and edge reflections. The proposed strategy is tested numerically, and validated through an experiment in which guided waves are actuated in a plate by four piezoelectric transducers operating simultaneously.